Medications and Patient Characteristics Associated with Falling in the Hospital - O’Neil, Caroline A. (J Patient Saf, 2018)
OBJECTIVES: To evaluate specific medications and patient characteristics as risk factors for falling in the hospital. METHODS: Case-control study comparing demographic, health, mobility, and medication data for 228 patients who fell between 6/29/2007 and 11/14/2007 at a large tertiary care hospital and 690 randomly-selected control patients. Logistic regression was used to identify fall risk factors. RESULTS: Independent risk factors for falling included: history of falls (OR, 2.7; 95% CI, 1.8 – 4.2); needing an assistive device (OR, 3.2; 95% CI, 1.5 – 6.8) or person assistance (OR, 2.1; 95% CI, 1.3 – 3.3) to ambulate; being underweight (OR, 2.4; 95% CI, 1.2 – 4.7) or obese (OR, 1.6; 95% CI, 1.0 – 2.5); confusion (OR, 2.4; 95% CI, 1.5 – 4.0); dizziness (OR, 2.1; 95% CI, 1.1 – 4.3); incontinence (OR, 1.5; 95% CI, 1.0 – 2.3); and an order for a hydantoin (OR, 3.3; 95% CI, 1.3 – 8.0) or benzodiazepine anticonvulsant (OR, 2.2; 95% CI, 1.5 – 3.3), haloperidol (OR, 2.8; 95% CI, 1.2 – 6.8), tricyclic antidepressant (OR, 2.4; 95% CI, 1.2 – 4.9) or insulin (OR, 1.5; 95% CI, 1.0 – 2.1). Female gender (OR, 0.8; 95% CI, 0.6–1.0), proton pump inhibitors (OR, 0.6; 95% CI, 0.4 – 0.9), and muscle relaxants (OR, 0.4; 95% CI, 0.3 – 0.7) were associated with lower risk of falling. CONCLUSIONS: This study identified medications and patient characteristics associated with increased risk for falling in the hospital. High-risk medications identified in this study may serve as targets for medication review or adjustment, which have been recommended as a component of multifaceted fall prevention programs.